2000
DOI: 10.1007/pl00006657
|View full text |Cite
|
Sign up to set email alerts
|

Imaging active lymphocytic infiltration in coeliac disease with iodine-123-interleukin-2 and the response to diet

Abstract: Coeliac disease is diagnosed by the presence of specific antibodies and a jejunal biopsy showing mucosal atrophy and mononuclear cell infiltration. Mucosal cell-mediated immune response is considered the central event in the pathogenesis of coeliac disease, and untreated coeliac patients show specific features of T-cell activation in the small intestine. Here we describe the use of iodine-123-interleukin-2 scintigraphy in coeliac patients as a non-invasive tool for detection of lymphocytic infiltration in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 11 publications
0
28
0
3
Order By: Relevance
“…Instead, radiolabeled IL-2 has optimal characteristics for in vivo detection of activated T cells in infiltrated tissues. It allowed detection of insulitis in two animal models of autoimmune diabetes, and a positive correlation between 123 I-IL-2 scintigraphic uptake and the degree of lymphocytic infiltration was observed by gamma camera imaging and proved histologically (9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, radiolabeled IL-2 has optimal characteristics for in vivo detection of activated T cells in infiltrated tissues. It allowed detection of insulitis in two animal models of autoimmune diabetes, and a positive correlation between 123 I-IL-2 scintigraphic uptake and the degree of lymphocytic infiltration was observed by gamma camera imaging and proved histologically (9)(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in patients with celiac disease it was possible to detect jejunal infiltration and to monitor the effect of diet on the immune process (9). Specific binding of radiolabeled IL-2 to activated lymphocytes was also clearly demonstrated by ex vivo microautoradiography and immunostaining; tissue specimens revealed that jejunal accumulation of 99m Tc-IL-2, as measured in vivo by single photon emission computerized tomography (SPECT), correlates with the number of infiltrating activated mononuclear cells per millimeter of mucosa (9). Similar results were achieved in patients with active Crohn's disease in whom 123 I-IL-2 scintigraphy was used to monitor the efficacy of therapy with corticosteroids (10).…”
mentioning
confidence: 99%
“…In vivo imaging of chronic inflammatory processes would help to overcome some of these limitations by providing direct evidence of the immune process and might contribute to the management of patients with autoimmune diseases [7,8]. 123 I-labelled IL2 ( 123 I-IL2) has been shown to detect with high accuracy lymphocytic infiltration in a series of patients with immune-mediated diseases [2,3]. Owing to, however, the cost of 123 I-IL2, only a limited number of Tc-IL2 patients can be studied; 123 I, moreover, is not readily available, and the preparation of 123 I-IL2 is a lengthy multistep procedure that requires the availability of a dedicated radiochemistry laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with 123 I-labelled IL2 ( 123 I-IL2) in several patients with immune-mediated diseases showed specific targeting of tissues-infiltrated by activated lymphocytes; rapid clearance from the circulation through the kidneys was observed, and major organs of uptake were kidneys, liver and spleen with minimal intestinal excretion. No side effects were reported [2,3]. Radiolabelled IL2 might be a useful radiopharmaceutical in different immune-mediated diseases: it might guide the diagnosis and treatment of the disease by providing relevant information about the presence of the ongoing inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…Exvivo autoradiographic examinations demonstrated the specific binding of 123 I-IL2 to activated lymphocytes in the inflamed gut mucosa (Signore et al, 1999a). In another study in the patients with coeliac disease, a positive correlation was observed between the uptake of 123 I-IL-2 measured by gamma camera and the number of histologically determined IL-2 receptor-positive cells in the inflamed jejunal mucosa (Signore et al, 1999b). Similarly,99m Tc-labelled IL-2 also showed specific accumulation in the inflamed tissue in several diseases such as insulin dependent diabetes (Signore et al, 1996) and melanoma (Barone et al, 1998).…”
Section: Interleukinmentioning
confidence: 90%